Influences of Personality on Ungulate Migration and Management - Found, Robert; St. Clair, Colleen Cassady (Frontiers in Ecology and Evolution, 2019)
Loss of migratory behaviour in ungulates often occurs with habituation to people to cause several challenges for wildlife managers, particularly in protected and urban areas. Aversive conditioning to increase ungulate wariness towards people could be an important tool for managing this problem, but it is frequently thwarted by variation in responsiveness among individuals, an aspect of personality that is currently little understood by managers. In this paper, we describe the potential role of personality in the ecological progression associated with habituation, loss of migration, and human-wildlife conflict in ungulates. We do so by (a) synthesizing our prior work on two populations of wild elk (Cervus canadensis) living in national parks in the Canadian Rocky Mountains, (b) using it to articulate a conceptual model to explain how anthropogenic changes in landscapes favour bolder individuals, and (c) showing how targeted use of aversive conditioning could limit the advantages to bold individuals that promote residency. Our review showed how bolder elk, defined by a combination of seven separate personality metrics on a bold-shy continuum, are three times more likely to forego migration, but are also quicker to learn by association, whether via the provision or cessation of aversive conditioning. These differences may relate to cognitive flexibility, which we measured with limb use preferences, to imbue bolder elk with more rapid responses to changing environments. In our conceptual model, we show how four ecological drivers comprised by interactions with humans, predators and conspecifics, in addition to changes in forage, favour bolder elk that are more likely to adopt a resident migratory tactic. We also explain how bold personalities could result from behavioral flexibility, genetic differences, or gene-environment interactions, each of which could be moderated by frequency-dependent payoffs to individuals. We suggest that managers could limit the prevalence of bold, resident ungulates by targeting bolder individuals with active and specific aversive conditioning, while minimizing anthropogenic food sources in predator refugia. A better understanding of personality in wildlife could support more proactive strategies to limit habituation and encourage migration and other keystone behaviours in changing landscapes.